Dasar Sukses ber-Yadnya dalam Tari Topeng Sidakarya di Bali - Renawati, Pande Wayan (Jurnal Lektur Keagamaan, 2014)
Bali is famous for all yadnya ceremony, full of art and culture is created by full-adi noble charm as relics of the ancestors of Indonesia. Was in the ceremonial procession to always use the big dance that are sacred also entertain the audience. One of the sacred dance that is danced Mask Dance Sidakarya after the ceremony is completed. Sidakarya Mask Dance is a mask dance that is danced to the realization of success in any yadnya ceremony in Bali. It begins with the sacred journey of a pastor from Java to Bali, until the establishment of Pura Dalem Sidakarya Sidakarya village located in Denpasar. Since the establishment of the temple, on the orders of the clergy, each resident who will carry out the ceremony to invoke tirtha or holy water to the temple and if the ceremony can present a rather large Sidakarya mask dance at the end of the ceremony as a sign of the success of the ceremony. It was described in the Chronicle Sidakarya. Keywords: Chronicle Sidakarya, Mask Dance Sidakarya.